2019
DOI: 10.3201/eid2501.180267
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Full-Genome Characterization of Nipah Viruses from Bats, Bangladesh

Abstract: Despite molecular and serologic evidence of Nipah virus in bats from various locations, attempts to isolate live virus have been largely unsuccessful. We report isolation and full-genome characterization of 10 Nipah virus isolates from Pteropus medius bats sampled in Bangladesh during 2013 and 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…In the current study, observed seroprevalence patterns and the fitted model suggest that three periods of transmission occurred over the 6 y of sampling, each of which followed periods of low adult and juvenile seroprevalence. Viral detection in bats has coincided with some human outbreaks, supporting the hypothesis that spillover is a sporadic event (67,97). In our study periods, low seroprevalence in bats was not always followed by outbreaks in humans.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the current study, observed seroprevalence patterns and the fitted model suggest that three periods of transmission occurred over the 6 y of sampling, each of which followed periods of low adult and juvenile seroprevalence. Viral detection in bats has coincided with some human outbreaks, supporting the hypothesis that spillover is a sporadic event (67,97). In our study periods, low seroprevalence in bats was not always followed by outbreaks in humans.…”
Section: Discussionsupporting
confidence: 86%
“…This finding was supported by an additional analysis of near-whole N gene sequences (∼1,720 nt) from bats, pigs, and humans, including those from a subset of P. medius from this and a more recent study by our group (SI Appendix,Fig. S5)(67). Eleven 224-nt N gene sequences obtained from bats between 2006 and 2012 (all from the Faridpur population) were identical.…”
supporting
confidence: 75%
“…The reservoir hosts of NiV have been identified as the large flying fox (P. vampyrus) and small flying fox (P. hypomenalus) in Malaysia [42,43] and the Indian flying fox (P. giganteus) in Bangladesh and India [44,45]. After many years of unsuccessful attempts, NiV was isolated from the Indian flying fox in Bangladesh [46]. The current status of henipavirus transmission during outbreaks is summarised in Figure 2.…”
Section: Paramyxovirusesmentioning
confidence: 99%
“…During the Nipah encephalitis outbreak in Malaysia during 1999, pigs acted as an intermediate host between bats and humans [ 16 , 17 ]. NiV can also be transmitted from bats to humans without an intermediate host [ 18 ], for example, through consumption of fresh date palm sap contaminated with bat saliva or urine in Bangladesh [ 19 ], as bats visit and contaminate the date palm sap regularly during the night [ 20 ]. Subsequent communication of NiV to humans following person-to-person transmission of the virus is fatal [ 21 ].…”
Section: Introductionmentioning
confidence: 99%